PENINGKATAN HASIL BELAJAR AKUTANSI PEMERIKSAAN SALDO KAS KECIL DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING SISWA KELAS XI AKUTANSI 1 SMK NEGERI 1 SUBOH PADA SEMESTER GANJIL TAHUN PELAJARAN 2019/2020: SMK NEGERI 1 SUBOH - ANANG ARIFANDI (Dewan Pendidikan Bondowoso, 2021)
The objectives that can be conveyed in this study are whether the application of the Discovery Learning learning model can increase student motivation in accounting lessons for the Petty Cash Balance Examination material in Class XI Accounting.1 SMK Negeri 1 Suboh.This type of research is Classroom Action Research (CAR). CAR is an observation of learning activities in the form of an action, which is deliberately raised and occurs in a class together. Wina Sanjaya (2011) defines CAR as a process of studying learning problems in the classroom through self-reflection in an effort to solve these problems by carrying out various planned actions in real situations and analyzing any effects of the treatment. Suharsimi Arikunto (2007) explains that in collaborative research, the party who takes the action is the class teacher himself, while the researcher who observes the ongoing process of action is the researcher. The classroom action research used in this study refers to the Kemmis & McTaggrat Model which consists of four components, namely planning, acting, observing and reflecting.This research was carried out in the odd semester of the 2019/2020 academic year for 3 months, namely from October to November 2019 at SMK Negeri 1 Suboh which is located at Jl. Raya No. 3 Suboh, Buduan Village, Suboh District, Situbondo Regency Postal code 68354. The subjects in this class action research were students of class XI Accounting 1 SMK Negeri 1 Suboh in the odd semester of the 2019/2020 academic year with a total of 32 studentsIn this study, there are two types of data, namely qualitative data in the form of learning situations during the learning process using the discovery learning model and quantitative data in the form of daily test results.Based on the type of research data above, the data collection techniques were carried out in two ways, namely: 1) The test method, namely this method was used to obtain data on student learning outcomes. 2). Observation method, this method is used to obtain data about the situation of the implementation of learning with an activity-based approachData Analysis Method All data obtained from this study were analyzed qualitatively descriptively and quantitatively. Descriptive qualitative data in the form of sentences that provide descriptions of the learning process and discovery learning learning model. Quantitative data includes statistical data which includes average, maximum or minimum value, standard deviation according to success indicators.From the results of the research starting from the first cycle and second cycle, it can be concluded that the use of discovery learning learning models can improve learning outcomes of accounting for checking petty cash balances in class XI students of SMK Negeri 1 Suboh, this can be seen from the following research data: 1 ). Learning completeness, in the first cycle the amount of learning mastery is 62.50%, in the second cycle it increases to 84.38%. 2). The absorption of students in the first cycle was 69.06%, while in the second cycle it increased to 74.06%